Effectiveness of a novel interactive health care education tool on clinical outcomes and quality of life in acne patients: A randomized controlled pilot study. (3rd September 2015) - Wang, Audrey S.; Wu, Julie; Tuong, William; Schupp, Clayton; Armstrong, April W.
Abstract: Background : We developed an Internet-based education tool (My Personalized Application for health Care Education, MyPACE) to promote patient comprehension about acne. Objective : To determine if MyPACE improves clinical outcomes and quality of life in acne patients. Methods : Modeling the spaced education approach, 50 participants received weekly multiple-choice questions for 12 weeks. Those randomized to the intervention group received acne-related questions, while those in the control group received non-dermatologic health-related questions. Acne lesion counts and Dermatology Life Quality Index (DLQI) scores were recorded at initial enrollment and at 12 weeks. Results : Within-group analysis for the intervention group showed a significant mean change in inflammatory and non-inflammatory acne lesions per person (−3.2 ± 1.3, p  = 0.0219; −4.4 ± 1.8, p  = 0.0267, respectively). The control group only demonstrated a significant mean change in inflammatory lesions (−2.8 ± 0.80, p  = 0.0040). Both groups had statistically significant improvement in DLQI score. Compared with participants in the control group, those receiving acne-related questions experienced greater improvement in clinical outcomes and quality of life. Limitations : The small sample size limited our ability to detect statistically significant differences. Conclusion : Internet-based, disease-specific, spaced education tools may be more effective than non-targeted tools for improving clinical outcomes and quality of life.